Corporate Governance Characteristics and Financing Decisions of Listed Firms in Ghana - Doku, James Ntiamoah; Ametorwobla, Godsway Kofi; Boadi, Isaac; Adzoh, Francisca Adzoa (Journal of Comparative International Management, 2022)
This study examined the relationship between corporate governance attributes, firm-specific characteristics, and financing decisions of listed firms in Ghana using panel data for a nine-year time frame spanning 2011 to 2019. The study adopted multivariate regression analysis using Prais-Winsten regression, correlated panels corrected standard errors (PCSEs). The findings show that corporate board structures in Ghana play a significant role in influencing the financing decisions of listed firms on the Ghana Stock Exchange. Specifically, corporate boards with bigger sizes and more female representation prefer more debt financing of their assets. Also, the findings provide support for the Pecking Order Theory and identifiable firm-specific determinants of financing decision of listed firms. The evidence provided by this study is robust to alternative estimators. The outcome of this study further provides strong policy support for enforcing proper corporate governance features and gender diversity dimensions for corporations in Ghana.